Peran Pemerintah Terhadap Supply Chain Management Pada Produk Minyak Goreng - Syahfitri, Syahfitri; Amwa, Djauky Ridho; Aisyah, Siti (Universitas Labuhanbatu, 2022)
Since 2006, Indonesia is a country with nominations for the largest producer of palm oil or what is known as Crude Palm Oil (CPO) in the world. Indonesia has abundant palm oil stocks, but it becomes a problem starting from the scarcity of cooking oil and the falling value of CPO. This research was conducted with the aim of knowing how the government's role in supply chain management in cooking oil products, through the nature of research in descriptive analysis, using qualitative research methods that utilize sources from library research, namely searching for the truth through google, articles, journals, books that related and continuous with the title. The result of this research is that the government implements a policy that requires retail companies and basic food traders to sell cooking oil with the highest retail price of Rp. 14,000/ liter with a maximum purchase of 2 liters per person per day. As well as implementing policies by encouraging palm oil exports and using excessive palm oil stocks to be absorbed by the domestic biodiesel industry for the B30 program in order to overcome the falling CPO value.